2022
DOI: 10.3390/pharmaceutics14102092
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid-Based Nanomaterials Applied to Cancer: Where Are We Now?

Abstract: Cancer cells normally develop the ability to rewire or reprogram themselves to become resistant to treatments that were previously effective. Despite progress in understanding drug resistance, knowledge gaps remain regarding the underlying biological causes of drug resistance and the design of cancer treatments to overcome it. So, resistance acquisition remains a major problem in cancer treatment. Targeted therapeutics are considered the next generation of cancer therapy because they overcome many limitations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 212 publications
0
11
0
Order By: Relevance
“…Considering the protective function of HA to avoid metabolic clearance in long blood circulation, the strong affinity to the CD44 receptors overexpressed on the surface of many tumor cells, and the easy degradation by hyaluronidase (HAase) in the cell to release payload [ 30 ], HA was coated on the surface of UCNP@10PCN to serve as an active targeting ligand for the enhanced endocytosis of the nanoparticles. By using coordination and electrostatic interactions, we successfully conjugated HA on the surface of UCNP@10PCN to form the UCNP@10PCN@HA (UPH) nanoparticles, which was confirmed by dynamic light scattering and infrared spectroscopy ( Figures S5 and S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the protective function of HA to avoid metabolic clearance in long blood circulation, the strong affinity to the CD44 receptors overexpressed on the surface of many tumor cells, and the easy degradation by hyaluronidase (HAase) in the cell to release payload [ 30 ], HA was coated on the surface of UCNP@10PCN to serve as an active targeting ligand for the enhanced endocytosis of the nanoparticles. By using coordination and electrostatic interactions, we successfully conjugated HA on the surface of UCNP@10PCN to form the UCNP@10PCN@HA (UPH) nanoparticles, which was confirmed by dynamic light scattering and infrared spectroscopy ( Figures S5 and S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that dextran‐based mRNA delivery can induce high gene expression and low cytotoxicity and provide a promising strategy to treat breast cancer 192 . Hyaluronic acid, as a nonsulfated glycosaminoglycan, is composed of glucuronic acid and N ‐acetyl‐ d ‐glucosamine bound linked beta‐linkages with good bio‐compatibility and biodegradability 193 . Yan et al have found that hyaluronic acid‐based Wingless and the name Int‐1 (WNT) 16 mRNA can be delivered to human cartilage explants and antagonize canonical β‐catenin/WNT3a signaling, contributing to increased lubricin production and decreased chondrocyte apoptosis in osteoarthritis (OA) 194 .…”
Section: Nanoparticles For Mrna Deliverymentioning
confidence: 99%
“…192 Hyaluronic acid, as a nonsulfated glycosaminoglycan, is composed of glucuronic acid and N-acetyl-D-glucosamine bound linked beta-linkages with good bio-compatibility and biodegradability. 193 Yan et al have found that hyaluronic acid-based Wingless and the name Int-1 (WNT)…”
Section: Polymer-based Delivery Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Various polysaccharides or fragments thereof, including hyaluronic acid and chitosan, are widely used as platforms for paramagnetic CAs in diagnosis and image-guided drug delivery. These topics are covered in several excellent recent reviews [ 3 , 4 , 5 , 6 ] and therefore will not be discussed in the present review. MRI using glucose-based chemical exchange saturation transfer (glucoCEST/CESL) is developing as an interesting highly sensitive and metal-free diagnostic imaging procedure.…”
Section: Introductionmentioning
confidence: 99%